The impact of diabetes on children and adolescents in schools, and the difficulties they experience, in Sirte city. (Journal of Academic Research, 2019)
The aims of this observational study are to find the impact of diabetes disease in children and adolescents in schools. The survey conducted from the anticipated students , their parents' , school supervisor and doctors. The difficulties experienced with full integration, to define a series of suggestions, and recommendations to improve their situation.Parents of children aged 5-18 years with diabetes were eligible. Those who agreed to take part in completing of a self-reporting questionnaire which determined the effects of the disease on children, based on three aspects; as the survey divided into three parts: - Patient information, Information about diabetes and how to deal with it, and the factors that are the cause of  the disease.A total of 35 questionnaires were completed and validated, 7 diabetic students refuse to fill up the questionnaires’. 51% of cases are between 15 to18 years old and 60% of them are females. The majority of parents believed that teachers could recognize the symptoms of a mild hypoglycaemic episode. It may help by increasing awareness about the disease. Because their peers think that diabetic is  a contagious disses. The school health office is not present in all institutions. Training sessions on Type 1 diabetes, through increasing the number of nurses. The Best availability of resources from disease associations to schools and improved communication between school personnel and parents. Were identified as key factors that may improve the full integration of the diabetic child in this setting. Reopen the health office, which they could bring much help to the diabetic student and another infection.
Keywords: diabetes mellitus